Rights Fulfillment in Social Capital Among Kelantan Chinese Muslim - Mohd Ali, Adi Syahid (Journal of Social Transformation and Regional Development, 2019)
Chinese Muslim community are experiencing relationship conflicts with their family origin and Malay community. The relationship conflict are affects their social capital. This article investigate rights fulfillment in bonding social capital (family origin) and bridging social capital (Malay community). This study used a sequential explanatory mixed method design and the sampling method is convenience and snowballs sampling. A total of 75 respondents from Kelantan Chinese Muslim community were involved in this study, and 5 of them were selected as informants in qualitative studies. The data were collected using questionnaires and semi-structured interviews. The results revealed that only rights fulfillment in bridging social capital is frequently happened compared to bonding social capital. In addition, there is no significant difference in rights fulfillment in bonding and bridging social capital in term of duration of respondent embracing Islam. Hence, this study recommends that Chinese Muslims fulfill the rights in social capital to ensure that their social capital is increased and it can be used to ensure the development of their community can be implemented properly.